Tough decisions : cases in medical ethics - Freeman, John Mark.; McDonnell, Kevin (Oxford ; New York : Oxford University Press, 2001)
Life is full of tough decisions that must be made ethically and under the pressures of time. This book places readers in realistic situation where they experience the difficulties of making tough medical decisions. The cases are composites of actual cases the authors have seen or managed. In the role of decision-maker, the reader helps to determine what happens in the case as his or her decision often shapes the course of events and the patient's outcome. This gives a compelling sense of the pressures that bear on clinical decision-making. The authors assume that the reader wants to do the rig.
PART V-HEALTH CARE REFORM AND ETHICAL THEORYChapter 17. Affordable Health Care; Chapter 18. Ethical Theory and Medical Ethics; Chapter 19. Making Moral Decisions: A Process Approach
Includes bibliographical references (page 211).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Medical ethics -- Case studies; Clinical medicine -- Decision making -- Case studies; Decision making -- Moral and ethical aspects -- Case studies; Decision making; Medical ethics; Bioethics; Clinical medicine; Human experimentation in medicine; Adulthood; Children; Confidential communications; Financial disclosure; Do-not-resuscitate orders; Genetic engineering; Health care reform; Informed consent (Medical law); Medical care; Physician and patient; Human reproductive technology; Assisted suicide; Decision Making; Ethics, Medical; Bioethical Issues; Bioethics; Patient Dropouts; Truth Disclosure; Clinical Medicine; Human Experimentation; Adult; Child; Confidentiality; Disclosure; Ethical Theory; Euthanasia, Passive; Genetic Engineering; Health Care Reform; Informed Consent; Patient Care; Physician-Patient Relations; Reproductive Techniques, Assisted; Resuscitation Orders; Suicide, Assisted; Éthique médicale -- Cas, Études de; Médecine clinique -- Prise de décision -- Cas, Études de; Prise de décision -- Aspect moral -- Cas, Études de; Médecine clinique -- Prise de décision -- Études de cas; Prise de décision -- Aspect moral -- Études de cas; Prise de décision.; Éthique médicale.; Bioéthique.; Médecine clinique; Expérimentation humaine en médecine.; Adultes; Enfants; Secret professionnel; Divulgation financière.; Interruption de traitement; Génie génétique.; Services de santé -- Réforme.; Consentement éclairé (Droit médical)